THE EFFECT OF UTILIZATION OF ACTIVATED CARBON FROM RUBBER SEED SHELLS AND COAGULANTS FROM KEPOK BANANA PEELS IN WELL WATER OF KENTEN LAUT RESIDENCE TOWARDS PARAMETER Ph, TSS, TDS AND TURBIDITY - Amiliza Miarti; Isdaryanto Iskandar (Bajang Institute, 2022)
Water is basic necessity in our daily life. But in fact, the water sources used by surrounding communities in Kenten Laut residence’s wells are still murky and still do not meet the standard specifications for drinking water. This study aims to determine the effectiveness of using activated carbon from rubber shells and optimal coagulation from kepok banana peels in improving the water quality of residence’s wells by using the parameters of pH, TSS, TDS and turbidity. Based on the research which has been conducted, the optimum effectiveness that could be used to increase pH value with dose of 0.1 grams was the coagulants from kepok banana peels of 7.08, while the activated carbon results were close to alkaline. Meanwhile, for other parameters, the optimum effectiveness for improving the water is the dose of 0.5 grams of rubber seed shell activated carbon, it could reduce TSS up to 90.66%, TDS 91.04% and turbidity 97.37%. Meanwhile, by using coagulant from kepok banana peels the effectiveness was only TSS 73.33%, TDS 40.29% and turbidity 68.86%.